SPIRITUALITAS TEMPAT KERJA DAN DAMPAKNYA BAGI KEEFEKTIFAN ORGANISASI - Lianto .; William Chang (Jurnal Ledalero, 2016)
The main purpose of this research is to explore the deepest significance of workplace spirituality. The importance of this spirituality makes a more productive contribution to the workplace. Spiritual values motivate workers to dedicate themselves more for a better atmosphere of work. A critical literature review shows us that each organization should be spiritual-friendly. Workplace spirituality can increase individual creativity, organizational citizenship, sense of self-fulfillment of employees, honesty, trust, and organizational commitment. In short, the organizations that encourage workplace spirituality will experience enhanced organizational performance.